2020
DOI: 10.1080/08037051.2020.1787815
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and overweight associated with masked uncontrolled hypertension: a Hypertension Optimal Treatment (HOT) Sub-Study

Abstract: The Hypertension Optimal Treatment (HOT) Study investigated the relationship between target office diastolic blood pressure (BP) ≤80, ≤85 or ≤90 mmHg and cardiovascular morbidity and mortality in 18 790 patients aged 50-80 years. The home BP sub-study enrolled 926 patients and the aim was to clarify whether the separation into the BP target groups in the office prevailed in the out-of-office setting. The present study aimed to identify variables that characterized masked uncontrolled hypertension (MUCH) and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(57 reference statements)
1
6
0
1
Order By: Relevance
“…Similar findings have been reported from previous studies 28 55 56. About one-third (36.9%) of the patients with uncontrolled hypertension had a history of current smoking, similar to the findings from previous studies 57 58. Unlike in other studies, in the current study, smoking was not associated with uncontrolled hypertension possibly due to few numbers of patients who did report to have been smoking.…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings have been reported from previous studies 28 55 56. About one-third (36.9%) of the patients with uncontrolled hypertension had a history of current smoking, similar to the findings from previous studies 57 58. Unlike in other studies, in the current study, smoking was not associated with uncontrolled hypertension possibly due to few numbers of patients who did report to have been smoking.…”
Section: Discussionsupporting
confidence: 91%
“…[ 24 ] The Hypertension Optimal Treatment (HOT) study also found UHT to be associated with tobacco smoking. [ 25 ] However, the prevalence of UHT (among those taking medication for hypertension) was not significantly different among smoked and smokeless tobacco users. This could mean that tobacco use is a significant risk factor for having high BP, while its association with UHT, though aPR >1, was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is a risk factor for cardiovascular disease, and smoking is associated with hypertension 30,31 . In this study, the result of the logistic regression analysis showed that smoking behavior were risk factor to hypertension, the OR of personal taste was 1.256.…”
Section: Discussionmentioning
confidence: 99%